2024
DOI: 10.1001/jamanetworkopen.2024.5479
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward COVID-19 Vaccines Among Pregnant and Recently Pregnant Individuals

Joshua T. B. Williams,
Kate Kurlandsky,
Kristin Breslin
et al.

Abstract: ImportancePregnant people and infants are at high risk of severe COVID-19 outcomes. Understanding changes in attitudes toward COVID-19 vaccines among pregnant and recently pregnant people is important for public health messaging.ObjectiveTo assess attitudinal trends regarding COVID-19 vaccines by (1) vaccination status and (2) race, ethnicity, and language among samples of pregnant and recently pregnant Vaccine Safety Datalink (VSD) members from 2021 to 2023.Design, Setting, and ParticipantsThis cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Thus, the COVID-19 vaccine is recommended for routine administration in all 3 trimesters of pregnancy . Since their introduction in December 2020, studies have demonstrated the safety of the messenger RNA (mRNA) COVID-19 vaccines in pregnant populations for a range of maternal and infant outcomes; nevertheless, many pregnant people remain hesitant about vaccination due to lingering concerns regarding safety …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the COVID-19 vaccine is recommended for routine administration in all 3 trimesters of pregnancy . Since their introduction in December 2020, studies have demonstrated the safety of the messenger RNA (mRNA) COVID-19 vaccines in pregnant populations for a range of maternal and infant outcomes; nevertheless, many pregnant people remain hesitant about vaccination due to lingering concerns regarding safety …”
Section: Introductionmentioning
confidence: 99%